2005
DOI: 10.5194/angeo-23-1533-2005
|View full text |Cite
|
Sign up to set email alerts
|

Pc5 modulation of high energy electron precipitation: particle interaction regions and scattering efficiency

Abstract: Abstract. Using the NORSTAR riometer and CANOPUS magnetometer arrays we have investigated the modulation of high energy electron precipitation by ULF waves in the Pc5 frequency band. We conducted two separate studies of Pc5 activity in the riometers. The first is an independent survey of three riometer stations in the Churchill line (one at each subauroral, auroral, and typical polar cap boundary latitudes) in which we identified all riometer Pc5-band pulsations over 11 years. All had a corresponding magnetome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 17 publications
2
54
0
Order By: Relevance
“…Nosé et al [1998] used DE-satellite and ground magnetometer and riometer data to argue that the riometer signature, accompanying Pc5 pulsations was due to parallel accelerated electrons in FLRs. However, contrary to that, Spanswick et al [2005] using the NORSTAR riometer and CANOPUS magnetometer arrays, and CRRES satellite concluded that high energy electron precipitation associated with Pc5pulsations is caused by pitch angle scattering. The relationship between quasi-periodic VLF emissions and geomagnetic pulsations has been discussed by some authors [e.g., Kimura, 1974;Manninen et al, 1996].…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Nosé et al [1998] used DE-satellite and ground magnetometer and riometer data to argue that the riometer signature, accompanying Pc5 pulsations was due to parallel accelerated electrons in FLRs. However, contrary to that, Spanswick et al [2005] using the NORSTAR riometer and CANOPUS magnetometer arrays, and CRRES satellite concluded that high energy electron precipitation associated with Pc5pulsations is caused by pitch angle scattering. The relationship between quasi-periodic VLF emissions and geomagnetic pulsations has been discussed by some authors [e.g., Kimura, 1974;Manninen et al, 1996].…”
Section: Introductionmentioning
confidence: 79%
“…Moreover, the statistical results, obtained by Spanswick et al [2005], suggest there is a localized region in the pre-noon magnetosphere where Pc5 band ULF activity can modulate high-energy electron precipitation, and a necessary condition for the pulsations observed by riometer is magnetic pulsations.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Roldugin and Roldugin [2010] studied 12 events of Pc4-5 pulsations recorded during photometric observations within the 2007-2008 polar night season in Spitsbergen, and in all events, similar auroral fluctuations were present. The occurrence of Pc5 fluctuations in the riometer absorption within a substantial data set was earlier mentioned by Spanswick et al [2005]: in the morning sector, 70 per cent Pc5 magnetic pulsations were accompanied by riometer pulsations. That the riometer pulsations do not occur in the other 30 per cent events may be explained by the fact that riometer's field of view is narrower than that of the magnetometer, or by a soft spectrum of precipitating particles when they do not reach the D region.…”
Section: Introductionmentioning
confidence: 67%